Equitable ecology: collaborative learning for local benefit in Amazonia - Shanley, P.; Rodrigues Gaia, G. (2002)
Rapid growth of timber, mining and ranching industries in forested areas worldwide often offer small holders opportunities to sell forest resources. Rural communities, however, often have little notion of the market value or economic and ecological consequences of forest transformation. Within such scenarios, the learning process needs to be consciously constructed so as to catalyse new ways of thingking about forest management effectively and quickly. This article describes an ecological research project that integrated data and process-oriented approaches to promote collaborative learning. Results indicate that user-centered approaches are needed to ensure that locally relevant information is generated by scientists, and that learning is catalysed not only among information saturated stakeholders such as policy makers and academics, but also among stakeholders who are directly dependent upon forest resources.